An Ambition to Redeem His Guilts of Amir in Khalid Hosseini’s “The Kite Runner” - Ahmat Jaelani (Hasanuddin University, 2024)
This study not only investigates the concept of ambition in literature but also underscores its transformative impact on human existence. By adopting a descriptive qualitative approach and drawing data from the characters' dialogues in